Analysis of the Relationship between Household Life Cycle and Tourism Expenditure in Taiwan: An Application of the Infrequency of Purchase Model. (October 2015) - Sun, Pi-Chuan; Lee, Huei-Shan; Chen, Tzong-Shyuan
The infrequency of purchase (IP) model was used to explore the impact of financial factors, limiting factors, social status and household life cycle on family travel intention and travel expenditure in Taiwan. The empirical results indicate that family travel intention and level of expenditure vary at different stages of the household life cycle. Additionally, family incomes, the education level of the head of the household, women's employment and home ownership have significantly positive impacts on travel intention and level of expenditure. The findings also suggest that the presence of a family member's health problems or the number of seniors over 65 years of age in a household will reduce travel intention and thus the level of travel expenditure.